Effect of Independence, Professionalism and Experience on Audit Quality - Chintya Noverini; Thomas Firdaus Hutahaean; Aurelie Gustylia; Aprilla Veronica; Eric Gunawan (Kusuma Negara Business School, 2020)
This study aims to examine and analyze the influence of independence, professionalism, and experience on audit quality in the city of Medan. This research was conducted with a population and samples taken with saturated techniques which used the entire population as a sample. This study uses a questionnaire distribution technique. The data analysis model uses multiple linear regression, validation test, reliability test, normality test, multicolonierity test, and others to get the desired results assisted by the SPSS program. The results of the research on independence and experience have a significant effect on audit quality at KAP in Medan city, while professionalism does not have a significant effect on audit quality in KAP in Medan city.